2020
DOI: 10.3329/bjb.v49i3.50007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium on panicle structure and spikelet morphology of a double grained rice cultivar

Abstract: Influence of K on panicle structure and spikelet morphology of a double grained rice cultivar was evaluated. Results showed that K enhanced the plant height, leaf number, yield and yield contributing descriptors in double grained rice cultivar. The ratio of single-double grained spikelets on a panicle varied from 70 : 30 to 59 : 41. The position of spikelets on a panicle viz. primary vs. secondary branch, middle vs. upper or lower portion of panicle, had little effect on single-double grain ratio. However, K s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was observed that the double grained rice cultivar produced relatively taller plant stature than BRRI dhan49 in all spacing combinations (Table 3). Sarwar and Chanda (2018) and Sarwar et al (2020) also reported that the double grained rice cultivar had produced relatively taller plants. The tiller production behaviour of BRRI dhan49 was found better than the double grained rice cultivar in interaction with plant spacing.…”
Section: Interaction Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…It was observed that the double grained rice cultivar produced relatively taller plant stature than BRRI dhan49 in all spacing combinations (Table 3). Sarwar and Chanda (2018) and Sarwar et al (2020) also reported that the double grained rice cultivar had produced relatively taller plants. The tiller production behaviour of BRRI dhan49 was found better than the double grained rice cultivar in interaction with plant spacing.…”
Section: Interaction Effectmentioning
confidence: 96%
“…Though a single grained spikelet is produced from a mono-pistillate ovary in the rice floret, around 254 genotypes with clustered spikelets were found in 26 countries of South and South-East Asia (Anon., 2012; Guarino, 2012). The double grained rice cultivar could be used to boost up the rice production in Bangladesh as it is well adapted to the local environment (Sarwar et al, 2020). A lot of research and extension activities are being carried out to acknowledge the increasing food pressure with decreasing cultivable lands.…”
Section: Introductionmentioning
confidence: 99%